Detecção de betalactamases de espectro expandido (ESBL) em cepas de coliformes isoladas de carne de frango comercializada na cidade de Fortaleza, Ceará. - Souza, Germana Conrado de (2007)
The poultry processing industry depends on the biosafety and quality of the products offered to the population, and is the cheapest and more affordable source of proteins. The intensive production process of poultry products requires constant microbiological controls. This study was aimed to assess the microbiological conditions of this product and to perform an antimicrobial susceptibility test and the screening of ESBL-producing bacteria on the strains isolated from the collected samples. Between April and November 2006, 80 samples of fresh and freezed poultry meat marketed in the city of Fortaleza were collected. The microbiological protocol included an aerobic mesophile bacterial count, and the determination of the coliform MPN at 35oC and 45oC, according to the ANVISA (National Sanitary Surveillance Agency) resolution RDC 12 of January 02, 2001. The susceptibility test was carried out according to the disk diffusion technique (KIRBY-BAUER), and the screening for ESBL-producing strains was performed by CLSI. The used antibiotics were amikacine (30µg), ampicillin (10µg), ciprofloxacin (5µg), ceftazidime (30µg), streptomycin (10µg), doxycycline (30µg), gentamicin (10µg), imipenem (10µg), sulphonamide (300µg) and sulfamethoxazol/trimetroprim (25µg). The mesophile bacterial count in the 80 tested strains ranged from <1.0 x 10 CFU/g to 6.3 x 10 CFU/g. 34 (43%) of the samples were positive for coliforms at 35oC and 17 (21%) for coliforms at 45oC. In the 11 E. coli strains, the highest resistance was found against doxycycline (91%), while 27% of the strains were 100% sensitive to amikacin, gentamicin and imipenem. Within the 22 Klebsiella pneumonia isolated strains, the highest resistance was against ampicillin (94.5%), with the highest sensitivity to gentamicin, sulfamethoxazol/trimetroprim and amikacin (94.5%, 94.5%, and 90%, respectively). Of the 19 Enterobacter aerogenes strains, 90.1% were resistant to ampicillin and 95.4% showed to be sensitive to ciprofloxacin. Of the 11 strains of Escherichia coli, 22 of Klebsiella pneumoniae and 19 of Enterobacter aerogenes, only 4, 9 and 5 strains, respectively, showed to have an ESBL-producing phenotype, and only 3 (33%) of the K. pneumoniae strains and 3 (60%) of the E. aerogenes strains were confirmed as being ESBL producers. We verified the poultry meat to be microbiologically flawed, as shown by the high number of mesophile aerobic bacteria and coliforms grown at 35oC and at 45oC, being a warning sign for the occurrence of DTA, even by microorganisms resistant to multipleantibiotics and ESBL producers. The implementation of a Hazard Analysis and Critical Control Points (HACCP) system involving all the processing stages can be an effective measure in order to improve the quality and safety of this product.